Morfologinių lietuvių, norvegų ir suomių kalbų kauzatyvų sintaksė - Rackevičienė, Sigita (Kalbotyra, 2004)
The article makes an attempt to analyse syntactic constructions formed by morphological causatives in Lithuanian, Norwegian and Finnish and to ascertain what types of causative constructions are characteristic of the languages under investigation.